THE ROLE OF ENVIRONMENTAL LITERACY IN SHAPING STUDENTS' ECOLOGICAL AWARENESS - Hakim, Lukman; Suranto, Suranto (Tahta Media Group, 2024)
This study aims to analyze the role of environmental literacy in shaping students’ ecological awareness at SMK Muhammadiyah Delanggu. The research employed a qualitative approach with a case study design. Data were collected through in-depth interviews, participatory observation, and documentation, and analyzed using thematic analysis involving data reduction, data display, and conclusion drawing. The findings indicate that environmental literacy plays a significant role in fostering ecological awareness through four main aspects: the development of ecological thinking patterns, the strengthening of moral responsibility based on religious values, the transformation of collective environmental behavior within the school environment, and the formation of a pro-environmental social identity. However, the consistency of environmentally responsible behavior remains a challenge, particularly beyond the school setting. This study highlights that environmental literacy integrated with school culture and religious values has strategic potential in building sustainable ecological awareness among vocational high school students.